Analysis of the effect of attacks with weapons in competitive activities fencers qualifications. - Bakum A.V.; Sergienko K.N. (Fizičeskoe Vospitanie Studentov, 2011)
Studied indices of volume and effectiveness of attacks with the action of the weapon in the arsenal of foil fencers in the competition activity at the present stage of development of fencing. The study analyzed 30 duels foreign and domestic highly skilled fencers. Established that the attacks with the action of the weapon occupy a leading place among other types of attacks in a highly competitive activity fencers. Determined that in duels fencers from the total number of attacks the volume of attacks with the action of the arms was 21.5%, with a productivity of 27,6%.